Implementation minimal service standards in outpatients hospital district Bogor - Suminah Suminah; Nasser Kelly (Universitas Katolik Soegijapranata Semarang, 2019)
Minimum Service Standards were made to serve as guidance for regions in organizing hospitals. The standards were then used as working indicators by the hospital management. In the field of health, the Minimum Service Standards were regulated by Health Minister’s Decree Nr. 43 of 2016. It was used as a tool to ensure even basic services access and quality to the community that was established and accountable to the Central Government. The Minimum Health Service Standards were very important for hospital’s outpatients in relation with the services provided and were closely related to the outpatient’s protection. This research applied socio-legal approach having analytical-descriptive specification. The data were gathered by having interviews to some resources, namely Head of Health Office of Bogor District, Director of Mary Hospital of Cileungsi Hijau, Unit Head of Sentosa Hospital of Parung.The results of the research showed that the Health Minister’s Decree Nr. 43 of 2016 on Minimum Service Standards in Health Field had not well implemented. The absence of minimun service standards setting issued by the Local Government, namely Bogor District, had made the health services run the minimum service standards in accordance with the existing regulations that referred to Health Office’s Strategic Planning (Renstra) and Health Minister’s Regulation on Hospital Classification and Permit. Bogor District should refer to the Health Minister’s Decree Nr. 43 of 2016 on Minimum Service Standards in Health Field so that the implementation of minimum services standards to outpatients could be well performed.